1923 N.H. Laws 138, § 4 - (:unkn) unknown (My University, 1923)
No person shall carry a pistol or revolver concealed in any vehicle or upon his person, except in his dwelling house or place of business, without a license therefor as hereinafter provided.
Keywords: CARRY